Voltage-type Г-source inverters - Loh, Poh Chiang (2013)
A new family of voltage-type Γ-source inverters is proposed in this paper. It uses a unique Γ-shaped impedance network for boosting its output voltage in addition to its usual voltage buck mode inherited from a traditional voltage-source inverter. Comparing with other techniques, the proposed inverters use lesser components, while yet producing flexible enhanced gains. Gain tuning is effected here by varying the turns ratio γΓZ of a coupled transformer, which always falls within the minimal range of 1 <; γΓZ ≤ 2. It therefore uses lesser winding turns, while yet producing the same high gain as its comparable correspondences. Theories and experimental results are presented for verifying the performances of the proposed inverters.